Benefits of health reform for households in rural South Africa following implementation of ward-based primary healthcare outreach teams: a qualitative inquiry - Landiwe Khuzwayo; Mosa Moshabela (Taylor & Francis Group, 2018)
Background: Major national primary healthcare reforms are seldom implemented, and few studies have explored the benefits of primary healthcare outreach teams to rural households, a knowledge gap we sought to address with this study. Objective: The objective of this study was to explore the community benefits in the context of PHC services delivered in rural households by outreach teams. Methods: The study was conducted in the iLembe District on the east coast of KwaZulu-Natal, South Africa between July 2015 and January 2017. In-depth, explorative and semi-structured qualitative interviews were conducted as part of a mixed-method study. A total of 21 in-depth interviews with key informants and four focus group discussions (n = 28) were conducted with purposefully sampled households and outreach team members. Content analysis was used to explore and understand the households' experiences of primary healthcare services provided by outreach teams. Results: Household members benefited from outreach team services tailored to specific households and individuals, which improved the efficiency of healthcare services, access to appropriate health information and the overall experience of healthcare, particularly among those who are physically unwell, on chronic treatment, default treatment or immunisation, or who need referrals for clinical and social services. The benefits to household members included personalised care in the home, improved referral pathways, awareness of health events, improved adherence to treatment and reduction in opportunity costs of healthcare. Conclusion: It is perceived that participants have benefitted from the model of PHC service delivery by outreach teams through improved access to healthcare services, and by allowing community members to receive services that are responsive to their needs since the outreach team members' advocate and negotiate to deliver services on behalf of community members. These stated benefits, as perceived by household members, have the potential to improve health outcomes and increase satisfaction levels amongst household members.